2015
DOI: 10.4236/as.2015.69091
|View full text |Cite
|
Sign up to set email alerts
|

Farmers’ Perception and Impact of Rice Yellow Mottle Disease on Rice Yields in Burkina Faso

Abstract: Rice improvement for disease resistance has scarcely involved farmers' knowledge in Sub-Saharan Africa. A participatory rural appraisal was conducted in two main rice cultivation areas in Burkina Faso to assess farmers' awareness of rice production constraints with emphasis on rice yellow mottle disease (RYMD) and its management. Farmers' preference for rice varieties to be used in the breeding program was also assessed. Major concerns for rice cultivation as perceived by farmers were water shortage and RYMD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 23 publications
(27 reference statements)
5
14
0
Order By: Relevance
“…Rice ( Oryza sativa L.) is increasingly becoming a major food crop in sub-Saharan Africa (SSA). Globally, rice is one of the most widely cultivated cereal crops distributed across diverse geographical, ecological and climatic conditions [ 1 , 2 ]. Given the varied adaptations of rice genotypes, several accessions are available with wide phenotypic and genotypic diversity [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Rice ( Oryza sativa L.) is increasingly becoming a major food crop in sub-Saharan Africa (SSA). Globally, rice is one of the most widely cultivated cereal crops distributed across diverse geographical, ecological and climatic conditions [ 1 , 2 ]. Given the varied adaptations of rice genotypes, several accessions are available with wide phenotypic and genotypic diversity [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in Nigeria and Côte d’Ivoire, yield losses above of 90% have been reported in susceptible cultivars, Bouake 189 and FARO 29 ( Onwughalu et al, 2011 ; Soko et al, 2016 ), while in Sierra Leone, losses of 82% were reported on varieties PN 623-3, TOX 516-12-SLR, and ROK 3 ( Taylor et al, 1990 ). Most recently in Burkina Faso, losses of 84% were recorded on popular varieties, FKR56N, FKR62N, and TS2 ( Traoré et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of RYMV varies between rice-producing countries, probably because of multiple factors including transitions from subsistence production to large-scale intensive rice production, and the associated increase in the diversity of vectors involved in virus transmission. For example, the incidence and severity of RYMV in most of Uganda’s rice-growing areas is between 50 and 75% under rainfed lowlands ( Ochola and Tusiime, 2010 ), while in Burkina Faso, the incidence of the disease tends to be lower at 28% ( Traoré et al, 2015 ). In Côte d’Ivoire, the incidence is higher during the dry season than during the rainy season while the opposite is the case in Nigeria ( Heinrichs et al, 1997 ).…”
Section: Introductionmentioning
confidence: 99%
“…The infected plants show a reduction of height and fertility. RYMV causes high losses ranging from 25% to 100% depending on the virus strain, plant genotype, and growth stage of the plants ( 3 , 4 ). The transmission is mediated mechanically through agricultural practices, insects, or animals ( 5 7 ).…”
Section: Genome Announcementmentioning
confidence: 99%